Redox homeostasis via gene families of ascorbate-glutathione pathway - Pandey, Prachi; Singh, Jitender; Achary, V. Mohan Murali; Reddy, Mallireddy K. (Frontiers in Environmental Science, 2015)
The imposition of environmental stresses on plants brings about disturbance in their metabolism thereby negatively affecting their growth and development and leading to reduction in the productivity. One of the manifestations of abiotic and biotic stress conditions is the enhanced production of reactive oxygen species (ROS) which can be hazardous to cells. Therefore, in order to protect themselves against toxic ROS, plant cells employ the anti-oxidant defense system. The ascorbate-glutathione pathway (Halliwell-Asada cycle) is an indispensible component of the ROS homeostasis mechanism of plants. This pathway entails the antioxidant metabolites: ascorbate, glutathione and NADPH along with the enzymes linking them. The ascorbate-glutathione pathway is functional in different subcellular compartments and all the enzymes of this pathway exist as multiple isoforms. The expression of different isoforms of the enzymes of ascorbate-glutathione pathway is developmentally as well as spatially regulated. Moreover, various abiotic and biotic stress conditions modulate the expression of the enzyme- isoforms differently. It is the intricate regulation of expression of different isoforms of the ascorbate-glutathione pathway enzymes that helps in the maintenance of redox balance in plants under various abiotic and biotic stress conditions. The present review provides an insight into the gene families of the ascorbate-glutathione pathway, shedding light on their role in different abiotic and biotic stress conditions as well as in the growth and development of plants.